The effects of internal marketing mix on performance in a healthcare context. (2019) - Salehzadeh, Reza; Jamkhaneh, Hadi Balouei; Doosti, Shabnam
The purpose of this paper is to examine the effect of internal marketing mix on organisation performance. Statistical population includes the employees of a community health service delivering dental, community nursing, physiotherapy, psychology, social work and occupational therapy services across some sites in Tehran. For data analysis, 211 completed and usable questionnaires were used. Structural equation modelling (SEM) was applied to test the relationships among the research variables. The findings showed that strategic reward, internal communications, training and development, and leadership have a significant positive effect on performance.